PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. WENANG PERMAI SENTOSA - MEWOH, ANFFERNEY DALLEN; Pio, Riane J.; Sumayku, Sontje (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
PT. Wenang Permai Sentosa continues to create innovations and growth forcorporate excellence. In connection with it is important for PT. Wenang PermaiSentosa to continue to maintain the progress and excellence of his company bycreating organizational culture to be the basis, value and guidance for its employees(HR) which is as the main driver of the company in achieving business goals andprofitability. With strong organizational culture owned by employees then thecompany will continue to grow and survive. In general, the results of the analysisstates strongly agree to organizational culture and performance variables. This statesthe influence of organizational culture on the performance of employees of PT.Wenang Permai Sentosa is at a good level. With analysis test proved thatOrganizational Culture have positive effect on Employee Performance so thathypothesis accepted. So with the results of the authors concluded the factors thatmake the organizational culture effect on employee performance that employees havea commitment in the company and can work well with a team and understand whatthe company goals. The better the organization culture the employee has, the higherthe employee's performance. Thus this study proves that Organizational Culture hasa strong relationship to Employee Performance.Keywords : Organizational Culture, Employee Performance